Analisis Minat Belajar Siswa Kelas X-1 di SMAN 1 Kramatwatu pada Pembelajaran Biologi Materi Virus - Annisa Hidayah (Universitas Pendidikan Ganesha, 2024)
This research aims to analyze the learning interests of class X-1 students related to learning virus material in biology subjects. The method used in this research is a qualitative descriptive approach with data collection techniques in the form of questionnaires and observations. The data obtained was analyzed using scoring to reveal a clearer picture of students' interest in learning. The results of the research showed that students in class X-1 at SMAN 1 Kramatwatu showed high interest in studying virus material in the biology subject. This is shown by the enthusiastic and responsive attitude of students during learning activities. Students also seem focused and pay attention to the lesson so that the material can be easily understood. Students' interest in learning is influenced by several factors. Factors that influence students' interest in learning can be divided into two categories: internal factors, such as learning style and interest in learning, and external factors, including learning models, learning methods, and material studies. These factors are mutually involved in forming students' interest in learning about viruses in biology.